Degradation and kinetic study of Reactive blue BF-5G and Remazol red RB 133% dyes using Fenton and photo-Fenton process - Santana, Rayany Magali da Rocha; Nascimento, Graziele Elisandra do; Napoleão, Daniella Carla; Duarte, Marta Maria Menezes Bezerra (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The textile industry is responsible for the generation of highly colored effluents, which need adequate treatment. Thus, the advanced oxidative processes (AOP) have been used to degrade the dye and convert organic matter. In the present study, the degradation of the reactive blue dyes BF-5G and red remazol RB 133% were evaluated through Fenton and photo-Fenton processes (solar and sunlight). To determine the best working condition, the pH, peroxide concentration, iron concentration and time variables were evaluated by performing a kinetic study in this condition. From a preliminary study, it was verified that the Fenton and photo-Fenton processes, using different radiations, presented similar results, reaching a degradation of more than 98% for each dye. The factorial design indicated better results for a concentration of H2O2 of 10 mg . L-1, iron concentration of 5 mg . L-1 and time of 15 min, obtaining degradation above 88% for the studied dyes. A good kinetic adjustment was verified for a pseudo first order kinetic model (R2 = 0.9921 and 0.9867 for blue and red dyes, respectively). Ultimately, the study of chemi-cal oxygen demand indicated a conversion of 75.98% for the Fenton process, 86.63% photo-Fenton solar and 87.02% photo-Fenton sunlight.